2020
DOI: 10.1292/jvms.20-0261
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito-borne viruses, insect-specific flaviviruses (family <i>Flaviviridae</i>, genus <i>Flavivirus</i>), Banna virus (family <i>Reoviridae</i>, genus <i>Seadornavirus</i>), Bogor virus (unassigned member of family <i>Permutotetraviridae</i>), and alphamesoniviruses 2 and 3 (family <i>Mesoniviridae</i>, genus <i>Alphamesonivirus</i>) isolated from Indonesian mosquitoes

Abstract: Mosquitoes transmit many kinds of arboviruses (arthropod-borne viruses), and numerous arboviral diseases have become serious problems in Indonesia. In this study, we conducted surveillance of mosquito-borne viruses at several sites in Indonesia during 2016–2018 for risk assessment of arbovirus infection and analysis of virus biodiversity in mosquito populations. We collected 10,015 mosquitoes comprising at least 11 species from 4 genera. Major collected mosquito species were Culex quinquefasciatus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…The NGS was thus performed by combining pool supernatants to confirm JEV presence, followed by RT-PCR confirmation to identify the pool source. Supriyono et al 15 reported similar results with distinct CPEs observed in C6/36 cells that were mainly caused by mosquito viruses circulating in Indonesia. Furthermore, mosquito-specific flaviviruses presence may also disrupt the RT-PCR analysis targeting the flaviviruses' RdRP region.…”
supporting
confidence: 57%
“…The NGS was thus performed by combining pool supernatants to confirm JEV presence, followed by RT-PCR confirmation to identify the pool source. Supriyono et al 15 reported similar results with distinct CPEs observed in C6/36 cells that were mainly caused by mosquito viruses circulating in Indonesia. Furthermore, mosquito-specific flaviviruses presence may also disrupt the RT-PCR analysis targeting the flaviviruses' RdRP region.…”
supporting
confidence: 57%
“…BAV is thought to be a mosquito-borne virus that may be transferred by wind among infected mosquitoes ( Liu et al., 2010 ). Thus far, BAV have been isolated from 10 mosquito species belonging to 3 genera ( Aedes , Anopheles , and Culex ) collected in Indonesia, Vietnam, South Korea, and China (Gansu, Shanxi, Inner Mongolia, Liaoning, Beijing, Hubei and Yunnan) ( Nabeshima et al., 2008 ; Xia et al., 2018a ; Supriyono et al., 2020 ). In this study, 9 strains of BAV strains were isolated from two genera of mosquitoes ( Anopheles and Culex ).…”
Section: Discussionmentioning
confidence: 99%
“…A. aegypti and A. albopictus are commonly infected with ISVs ( Supplementary Figure 2 and Supplementary Table 1 ) (Hoshino et al, 2009 ; Rizzo et al, 2014 ; Vasilakis et al, 2014 ; Chandler et al, 2015 ; Fan et al, 2016 ; Fernandes et al, 2016 ; Sadeghi et al, 2017 ; Ajamma et al, 2018 ; Fang et al, 2018 , 2021a , b ; Iwashita et al, 2018 ; Parry et al, 2018 , 2021 ; Zakrzewski et al, 2018 ; Zhang et al, 2018 ; Gravina et al, 2019 ; Martin et al, 2019 , 2020 ; Shi et al, 2019 ; Baidaliuk et al, 2020 ; da Silva Ferreira et al, 2020 ; Diagne et al, 2020 ; Jeffries et al, 2020 ; Kubacki et al, 2020 ; Ramos-Nino et al, 2020 ; Ribeiro et al, 2020 ; Supriyono et al, 2020 ; Thannesberger et al, 2020 ; Batson et al, 2021 ; Chiuya et al, 2021 ; Hameed et al, 2021 ; He et al, 2021 ; Munivenkatappa et al, 2021 ; Nebbak et al, 2021 ; Yezli et al, 2021 ; Calle-Tobón et al, 2022 ; Coatsworth et al, 2022 ; Duarte et al, 2022 ; Oguzie et al, 2022 ; Palatini et al, 2022 ; Aragão et al, 2023 ; Bennouna et al, 2023 ) that may alter their vectorial competence (Bolling et al, 2015 ; Öhlund et al, 2019 ). Phasi Charoen-like virus (PCLV) and Humaita Tubiacanga virus (HTV) are common ISVs found in A. aegypti , and A. albopictus ( Supplementary Figure 2 ).…”
Section: Mosquitoes and Arbovirusmentioning
confidence: 99%